1990
DOI: 10.1210/endo-127-1-497
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Differentially Alters Transcapillary Movement of Intravascular Igfbp-1, Igfbp-2 and Endothelial Cell Igf-Binding Proteins in the Rat Heart

Abstract: Insulin-like growth factor binding-proteins 1 and 2 (IGFBP-1, IGFBP-2) and endothelial cell IGF binding proteins (ECBP) were individually perfused through isolated beating rat hearts in the absence and presence of insulin. Insulin caused an increased movement of IGFBP-1 from the vascular space to tissues of the heart. Subendothelial content of IGFBP-1 was 110%, 126% (p less than .01) and 132% (p less than 0.05) of control hearts when perfused with 1, 10 and 100 ng/ml insulin, respectively. . In contrast, insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(58 citation statements)
references
References 13 publications
4
53
0
1
Order By: Relevance
“…77, 82,84,86 There is some evidence that IGFBP-1 may enhance active transport of IGF-1 through the endothelial barrier, in response to a rise in insulin levels. 89,90 Alternatively, decreases in IGFBP-1 and IGFBP-2 may lead to an increase in plasma levels of free IGF-1, 91 ± 93 a small fraction of IGF-1 (`2%) that is unbound to IGFBPs or dissociates from them very readily, and that may easily diffuse into tissues. Plasma free IGF-1 correlates inversely with plasma IGFBP-1 and IGFBP-2, and positively with obesity and plasma insulin levels.…”
Section: Androgens the Androgen Hypothesismentioning
confidence: 99%
“…77, 82,84,86 There is some evidence that IGFBP-1 may enhance active transport of IGF-1 through the endothelial barrier, in response to a rise in insulin levels. 89,90 Alternatively, decreases in IGFBP-1 and IGFBP-2 may lead to an increase in plasma levels of free IGF-1, 91 ± 93 a small fraction of IGF-1 (`2%) that is unbound to IGFBPs or dissociates from them very readily, and that may easily diffuse into tissues. Plasma free IGF-1 correlates inversely with plasma IGFBP-1 and IGFBP-2, and positively with obesity and plasma insulin levels.…”
Section: Androgens the Androgen Hypothesismentioning
confidence: 99%
“…We next examined the potential roles of each binding site in the transendothelial transport of perfused IGF-I and the perfused binary complex of IGFBP-3 ⅐ IGF-I. It has been previously shown that both perfused IGF-I and IGFBP-3 cross the endothelial boundary and localize predominantly in cardiac muscle (1). Hearts were perfused with 125 I-IGF-I alone, 125 I-IGF-I plus IGFBP-3, and 125 I-IGF-I plus the IGF-I analog Long R 3 (LR 3 ) IGF-I.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that, in cultured endothelial cells, 125 I-IGF-I ⅐ IGFBP-3 complexes at a 1:10 ratio, a similar ratio as in the perfused hearts, bound minimally to the IGF-I receptors, suggesting that binary complexes in the beating heart may behave differently than when exposed to cultured cells. 1 Free IGF-I and IGF-I ⅐ IGFBP-3 binary complexes are present in the circulation (10), and the binary complex has been used in therapy (7). However, Ͼ90% of all IGF-I in the blood is contained in the ternary complex of IGF-I ⅐ IGFBP-3/acid-labile subunit (4).…”
Section: Discussionmentioning
confidence: 99%
“…These binding proteins modulate the egress of the IGFs out of the vascular space and may serve to limit the hypoglycemic effects of the IGFs (Meuli et al 1978, Bar et al 1990, Clemmons 1990). We have previously identified an acid protease activity present in rat serum and tissue extracts which is capable of catalyzing the conversion of IGF-I to the des(1-3) variant (Yamamoto & Murphy 1994).…”
Section: Introductionmentioning
confidence: 99%